A decision analysis model for smart mobility system development under circular economy approach. (April 2023) - Pamučar, Dragan; Durán-Romero, Gemma; Yazdani, Morteza; López, Ana M.
Abstract: Circular economy (CE) is recognized as one of the most popular theories of the decade. Its domain spreads to disciplines like production, environmental sciences, and transport/mobility sectors. This research corresponds to one of the essential questions in CE which look for effective solutions in smart mobility systems regarding eco-innovation indicators. We conducted a deep survey on CE and smart mobility literature and sorted out potential solutions (alternatives) and fundamental indicators based on the Quintuple Helix model. Then, a rough-based multiple criteria decision analysis model was adopted by the incorporation of LMAW (logarithm methodology of additive weights) and MARCOS (measurement of Alternatives and Ranking according to the COmpromise Solution) methods. To analyse the potential solutions, ten experts from relevant sectors assisted us in composing an assessment platform through qualitative comparison. Initial results showed that public transport (good practices) and shared mobility services are amongst the best solutions for establishing a smart mobility plan. Our decision-making model was tested and showed that our ranking scores are highly confidential and stable. The outcome of this study can be benchmarked in urban planning, where policymakers should rethink the transport and mobility sectors, structuring, development, and economic remodelling which are top decision-making problems nowadays.